Comparison of Beetroot and Red Guava Wellness Shots on Hemoglobin Levels in Pregnant Women at Samarang Health Center, Garut Regency - Rahmi Januarti, Nurul; Tiara Carolin, Bunga (International Journal of Midwifery and Health Sciences, 2025)
Background: Anemia in pregnant women is a serious health issue with a high prevalence of 61.8% in Garut Regency, Indonesia. Effective and safe interventions are needed to prevent pregnancy complications. Wellness shots made from beetroot and red guava, local food-based non-pharmacological treatments, have potential to increase hemoglobin levels by enhancing iron absorption. Purpose: This study aims to compare the effectiveness of beetroot and red guava wellness shots in improving hemoglobin levels among pregnant women with moderate anemia at Samarang Health Center, Garut Regency. Methods: A quasi-experimental design with a non-equivalent control group was conducted involving 44 third-trimester pregnant women with hemoglobin levels between 7.0 and 9.9 g/dL. Participants were divided into two intervention groups, each receiving wellness shots for 14 consecutive days. Hemoglobin levels were measured before and after the intervention using a digital hemoglobin meter. Data were analyzed using the Shapiro-Wilk test for normality, paired t-test, and independent t-test, with a significance level of p < 0.05. Results: Both groups showed significant increases in hemoglobin levels. The beetroot group’s mean hemoglobin increased from 8.69 to 9.56 g/dL, while the red guava group’s mean increased from 8.66 to 9.26 g/dL (p < 0.001). Comparison of post-intervention hemoglobin levels revealed a significantly greater increase in the beetroot group compared to the red guava group (p = 0.009). Conclusion: Wellness shots made from beetroot and red guava effectively increase hemoglobin levels in pregnant women with moderate anemia, with beetroot showing superior effectiveness.